The needs for coordination in sustainable urban infrastructure development - Yazdani, Saeid; Mohd Yusof, Mohd Johari; Dahlan, Nur Dalilah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Urban infrastructure systems shape the interactions between civilized society and the natural environment. Whilst these urban systems are the most visible impact of humanity upon the environment, sustainable development of them is also crucial to minimize the impacts of human activities on the environment. Coordination among different agencies involved in the urban infrastructure development is an essential factor to achieve sustainability in the process. Co-ordination is a key enabler that brings together these agencies to make their endeavors more compatible with the interests of environmental, economic and social aspects, the triple bottom line of sustainability. From a sustainability point of view, this paper by identifying and analyzing the effects of lack of coordination, aims to delineate the role coordination in the context of sustain-able urban infrastructure development.